Faktor-Faktor Yang Berhubungan Dengan Pengetahuan Suami Tentang Pendampingan Kehamilan Sehat Pada Ibu Primipara Trimester Pertama Di Wilayah Kerja Puskesmas Jembatan Kecil Kota Bengkulu - Handayani, Tita Septi; Samidah , Ida; Murwati, Murwati (Jurnal Pakar Kesehatan, 2025)
Based on Census Figure Survey data, it shows that the maternal mortality rate is around 305 per 100,000. It cannot be denied that caring for pregnant women during pregnancy is still a difficulty for the pregnant woman's family, especially the husband. Method: This study uses a systematic review method through relevant articles from Google Scholar with publication years 2007-2020. This article search was carried out using the Preferred Reporting Item for Systematics (PRISMA). This identification uses the Google Scholar database. Seen from the results of research in 10 journals, it shows that the level of husband's knowledge regarding pregnancy care is good, but the husband's role in domestic activities is still low, while the husband's social role in supporting pregnant women to participate in social activities is also still low. So there is a positive relationship between husband's support and the mother's motivation to pay attention to her pregnancy. It can be concluded that the success of pregnant women in undergoing the pregnancy process until delivery also depends on the role and support of the husband.